A Strategic Framework to Manage Ethical Dilemma in Corporate Governance - Walia, Nidhi; Kiran, Dr. Ravi (Indian Journal of Finance, 2007)
In the era of volatile global markets corporate sector has accepted the fact that now they have to operate in more competitive and challenging environment. Looking forward for bright future ahead corporate sector has realized their obligation towards society and to meet this demand they are ostensibly focusing to introduce concept of corporate governance in their business. Corporate governance mechanism is designed to monitor and control the organization affairs not only to add value towards sustainable return to shareholder’s wealth but concentrate on aligning business activity as per investor’s expectations. Thus corporate governance issues have become part of business activities whereby structures and processes are formulated for direction&control of companies finally encouraging effective planning and quality decision making. Present paper is an attempt to answer some fundamental questions raised about complex network of relationship among shareholders, Board of Directors, bankers, auditors etc. Results of the study have proved that in India corporate sector is still found to be in ethical dilemma regarding introduction of corporate governance practices. Finally study is concluded by suggesting that even the most developed countries, especially United States have acknowledged this fact that code of corporate governance envisages adherence to highest standard of honesty and integrity that result in adding value to wide spectrum of corporate clients.